Understanding Self-Regulated Learning and the Role of Mentoring in Learning Through a Workshop for Teacher in Hat Yai Thailand : Mengenal Self-Regulated Learning dan Peran Pembelajaran Mentoring melalui Workshop bagi Guru di Hat Yai Thailand - Nur Hidayati, Ratri; Priwantoro, Soffi Widyanesti; Agustin, Felanda Neshi (Borneo Educational Journal (Borju), 2025)
The important of students Self-Regulated Learning (SRL) in 21st century education requires teachers to provide learning process that support this skill. One learning model that can improve help students SRL is mentoring based learning. However, teachers in Thailand especially at Songserm Sasana Vitaya School, still do not have enough knowledge about how to mentoring can support students SRL. Therefore the aim of this community service was to conduct a workshop that introduce the concept of mentoring and its role in supporting SRL. The method began with a pre-test to determine preliminary understanding of teacher, followed by an online workshop using the zoom platform. In addition to the online workshop, an offline workshop was also held to conduct role play and gallery walk activities. Finally, a post-test was conducted to measure the increasing of teachers knowledge and skills.  The result of workshop showed 57,5% increase in teacher awareness that mentoring can help student become more independent. Meanwhile, the understanding that mentoring supports SRL improved from 11 % in the pre-test to 52,2% in the post-test. In addition, teacher’s responses to open-ended question changed from simple answers in the pretest to more complex and detailed answers in the post-test. Overall, the comparison between pre and post-test result shows a clear improvement in teachers understanding of the role of mentoring in enhancing student’s SRL.